Understanding the Influence of Mobile In-App Price Promotions in Food Delivery Apps on Customer Engagement and Advocacy - Rani Sharma, Devika; Singh, Balgopal; Jaiswal, Kamal (Indian Journal of Marketing, 2023)
Purpose : With the emergence of e-commerce, food ordering through mobile-app also witnessed significant growth akin to other products. However, the consumers’ switching rates for online food service provider was found to be high. Traditional marketing wisdom suggested various forms of promotion to counter this. The form of promotion mainly suggested was price promotion. The objective of the present study was to understand the role of in-app price promotion between consumer engagement and advocacy relationships in the context of food delivery applications. Methodology : The descriptive research design was adopted to further the study. A research model depicting the proposed hypotheses was developed based on social exchange and incentive theories. Data were collected through an online questionnaire from 293 users of food delivery applications from the Delhi-NCR region. PLS-SEM was used to test the hypothesized relationships between the constructs. Findings : The study established that in-app price promotion was positively associated with consumer advocacy and fully mediated the relationship between consumer engagement and advocacy. Practical Implications : This study strongly recommended that food delivery app managers should frequently offer in-app price discount coupons to their existing customers. Availing of promotional benefits would help spread positive word-of-mouth about food and service quality. Positive advocacy would be beneficial to attract new customers. This study would also be helpful to future researchers in the conceptualizing study in another e-commerce context. Originality : This study was the first to determine the role of in-app price promotion between consumer engagement and advocacy relationships in the online food-delivery app context.